A influência da perfusão cardíaca nas relações pressão/volume do ventrículo esquerdo. - Tucci, P. J.; Nogueira, R. J.; Tornero, M. T. (My University, 1993)
PURPOSE--To analyze the influence of the myocardial engorgement due to coronary perfusion on the left ventricular diastolic pressure/volume (P/V) relations. METHODS--The study was undertaken in the isovolumic blood-perfused dog heart preparation (n = 7). The P/V relations were determined promoting ventricular volumes variations by steps of 2ml, in two conditions: during coronary perfusion pressure of 100mmHg and after occlusion of the perfusion line. RESULTS--It was verified that the P/V relations obtained without myocardial perfusion shifted to the down right in respect to the perfused heart. A exponential fitting of the P/V relations allows to conclude that there was no difference among the slopes of the curves obtained with and without perfusion. CONCLUSION--Our results indicated that coronary perfusion restrain the capacity of the left ventricle to receive blood, but there is no influence on the passive elastic stiffness of the chamber. This effect was taught to be consequence of the myocardial erectile property.
Influence of cardiac perfusion on relations of pressure/volume of the left ventricle
Keywords: animal; comparative study; dog; heart left ventricle function; heart stroke volume; heart ventricle pressure; perfusion; physiology; time; Animal; Comparative Study; Dogs; English Abstract; Perfusion; Stroke Volume; Time Factors; Ventricular Function, Left; Ventricular Pressure